Diagnostic yield of repeat screening colonoscopy ten years after an adenoma-negative index screening endoscopy - v. Schönfeld, Philippa; Hauser, Daniel; Baldus, Stephan Ernst; Özer, Eda Yilmaz; v. Schönfeld, Jürgen (Zeitschrift für Gastroenterologie, 2022)
In Germany, colonoscopy was introduced as a screening instrument about 20 years ago. Ten years after an adenoma-negative index endoscopy, a second screening colonoscopy can be performed in younger persons, but this approach is based on limited evidence. We therefore prospectively analyzed the diagnostic yield of second screening colonoscopies in clinical routine.Ten years following adenoma-negative screening endoscopy a second screening colonoscopy was performed in 401 persons (210 women and 191 men); mean age was 70 years. A total of 244 benign neoplastic lesions were removed in 135 persons (34%). Eight persons had three or more small tubular adenomas removed; 19 persons had at least one tubular adenoma measuring ≥ 10 mm; 14 persons had adenomas with villous characteristics; 19 persons had serrated adenomas; one person had an adenoma with high grade dysplasia. Thus 61 persons (33 men and 28 women) were classified as bearing a significant risk for the development of colorectal cancer (15%). An additional patient had a low-risk malignant polyp removed endoscopically.We conclude that a significant number of small and advanced adenomas can be identified in a second screening colonoscopy ten years after an adenoma-negative index screening endoscopy, but malignant lesions are rare. Whether or not removal of the benign lesions in a second screening colonoscopy will reduce incidence and mortality of colorectal carcinoma remains to be seen in this elderly group.
Keywords: Vorsorgeuntersuchung; Koloskopie; Adenomerkennung; Kolorektalkarzinom